Bioinspired Devices : Emulating Nature's Assembly and Repair Process - Goldfield, Eugene C. (Harvard University Press, 2018)
Eugene Goldfield lays out principles of engineering found in the natural world, with a focus on how components of coordinated structures organize themselves into autonomous functional systems. This self-organizing capacity is one of many qualities which can be harnessed to design technologies that can interact seamlessly with human bodies.